Hedges and Booster in the Presidential Candidate Debate to Build the Candidate’s Image - Salsabilla, Fissilmi; Kurnia, Dea Tunjung; Octaviani, Retno Nur; Cahyono, Setyo Prasiyanto (Universitas Negeri Semarang, 2024)
This research analyzed use of Hedges and Booster in the Presidential Candidate Debate to Build the Candidate’s Image in the YouTube Livestreaming video published on 4th February 2024. In conducting this study, the researchers employ descriptive qualitative method to describe the phenomenon of the Hedges and Booster used in the final presidential debate. Meanwhile, the theoretical framework is the theory of Brown and Levinson in 1987. The findings of the study reveal that there are 391 Hedges used and 842 Boosters used by the candidate in the final presidential debate. They use hedges to maintain their languages in the hope that the audience can follow their arguments clearly. Meanwhile, the use of booster in the languages is to boost their arguments and to reveal their objectivity in delivering the arguments.